Predictive Analysis of Spatial Data and Time Series to Predict Earthquake Magnitudes by Using Data Mining Approach - Ignazio Ahmad Pasadana; Herman Mawengkang; Syahril Efendi (RIRAI Publisher, 2023)
The suggested methodology presented in this work uses data mining to identify seismic zones and time series to forecast earthquake magnitudes. Utilize historical earthquake data gathered from the United States Geological Survey (USGS) and obtained by utilizing hierarchical and fartherst first clustering to predict seismic activity. Latitude and longitude cluster data were used to create a prediction model to forecast the size of upcoming earthquakes in the Nanggroe Aceh Darussalam region and its nearby areas.